A case report of zinc phosphide poisoning: complicated by acute renal failure and tubulo interstitial nephritis - Nilukshana Yogendranathan; H. M. M. T. B. Herath; Thenuka Sivasundaram; R. Constantine; Aruna Kulatunga (BMC, 2017)
Abstract Background Run Rat® is a rodenticide widely used against small mammals. It comprises of a minimum of 32% zinc phosphide which is highly toxic in acute exposures to humans. It may be consumed accidentally or intentionally. It enters the body via skin, respiratory and gastrointestinal tracts. Zinc phosphide is hydrolyzed by the gastric acid and is transformed into phosphine gas. Phosphine is a respiratory toxin that inhibits cytochrome C oxidase system resulting in renal failure and liver failure. Case presentation A 35 year old Sri Lankan female presented following ingestion of 2.5 g of Run Rat®, which is a branded preparation of zinc phosphide, resulting in 61 mg/kg poison load. She developed severe acute kidney injury with acute tubular necrosis, subnephrotic ranged proteinuria and tubulointerstitial nephritis for which she underwent haemodialysis three times along with other measures of resuscitation. She also developed elevated liver enzymes with hyperblirubinaemia, hypoalbuminaemia, acute pancreatitis and mild myocarditis. She improved with supportive therapy over a period of 3 weeks. Conclusion Run Rat® is a commonly used rodenticide and the toxic effects are mediated through conversion of phosphide to phosphine gas. The majority of the deaths had occurred in the first 12 to 24 h and the main causes identified are refractory hypotension and arrhythmias. The late deaths (beyond 24 h) had been commonly due to adult respiratory distress syndrome, liver and renal failure. The outcome is poorer with delayed presentation, development of coagulopathy, hyperglycaemia and multiorgan failure with elevated liver enzymes. In our patient, Zinc phosphide poisoning caused severe acute kidney injury, abnormal liver profile, pancreatitis and possible myocarditis. The patient improved with repeated haemodialysis. The renal biopsy revealed acute tubulointerstitial nephritis with acute tubular necrosis. In tropical countries, the rural population engaged in agriculture has easier access to the compound, as it is available at a lower cost. Furthermore, the lack of an antidote and advanced resuscitative measures such as inotropic supportive therapy and renal replacement facilities at most of the peripheral hospitals pose a major challenge in providing timely interventions to prevent deaths.